A computational approach for explaining the effect of the prl gene polymorphism on prolactin structure and biological activity in Japanese quails. Issue 3 (1st June 2021) - Al-Shuhaib, Mohammed Baqur S.; Al-Kafajy, Fadhil R.; Al-Jashami, Ghadeer S.
Abstract: Prolactin is a versatile hormone with multiple activities, including a negative control on egg production. This study was conducted to genotype all the coding portions of the prl gene using PCR-SSCP-sequencing, and to investigate the effects of amino acid substitutions of the prl gene on the structure and function of prolactin in quails using in silico approach. Though all genotyped exons exerted homogenous PCR-SSCP patterns, a total of 12 novel SNPs were detected in the investigated exons, including three SNPs in exon-1, 8 SNPs in exon-2, and one SNP in exon-4. Three adjacent missense SNPs were detected in exon-2, namely H69P, T70P, and S71F. Computational tools indicated obvious deleterious effects of T70P, with less extent to H69P and S71F on prolactin functions and activity, which may lead to limited participation of this hormone in the negative control of egg production. In conclusion, the introduction of in silico prediction has suggested an alternative solution for the breeders to evaluate the effect of each witnessed nsSNP in protein structure and function. The current study suggests three nsSNPs, T70P, T70P, and S71F as strong candidates for the negative effect on prolactin biological activity with a consequent reversal positive effect on egg productivity traits.